Kejiko II Church and Government Forum Resolutions (Tufts Archival Research Center, 2005)
This document is about the resolutions reached in the Kejiko II Government and Church Forum that was held by the Sudan Council of Churches and the South Sudan government. The resolutions pertain to: the referendum and the post-referendum situation, the relation between state and church, and Abyei.